2021
DOI: 10.4062/biomolther.2020.048
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Suppresses Migration of Human Renal Carcinoma Caki-1 Cells through Inhibition of the PGE2-Mediated Activation of the EP2 Receptor Pathway

Abstract: Renal cell carcinoma (RCC) is likely to metastasize to other organs, and is often resistant to conventional chemotherapies. Thymoquinone (TQ), a phytochemical derived from the seeds of Nigella sativa , has been shown to inhibit migration and metastasis in various cancers. In this study, we assessed the effect of TQ on the migratory activity of human RCC Caki-1 cells. We found that treatment with TQ reduced the proteolytic activity of matrix metalloproteinase-9 (MMP-9) in Caki-1 cells. TQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Targeting invasion and migration are especially essential for malignancies that currently lack specific treatments, such as TNBC [ 52 ]. Several studies have reported the role of TQ in cancer cell migration [ 53 , 54 , 55 , 56 ]. The authors noted that TQ inhibits the migration and invasion of prostate cancer [ 57 ] and BC [ 58 ] in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting invasion and migration are especially essential for malignancies that currently lack specific treatments, such as TNBC [ 52 ]. Several studies have reported the role of TQ in cancer cell migration [ 53 , 54 , 55 , 56 ]. The authors noted that TQ inhibits the migration and invasion of prostate cancer [ 57 ] and BC [ 58 ] in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“… 45 Natural compounds, such as shikonin and thymoquinone (TQ), have also been shown to exert anti‐RCC effects by modulating the PI3K/AKT signaling pathway. 46 , 47 Shikonin inhibits RCC cell proliferation in a dose‐dependent manner and induces apoptosis by activating the Ras/MAPK and PI3K/AKT signaling pathways. 46 Similarly, TQ inhibits RCC cell migration by suppressing the activation of the prostaglandin E2 ( PGE2 )‐mediated EP2 receptor– PI3K/AKT axis.…”
Section: Signaling Pathways In Renal Cancermentioning
confidence: 99%
“… 46 Similarly, TQ inhibits RCC cell migration by suppressing the activation of the prostaglandin E2 ( PGE2 )‐mediated EP2 receptor– PI3K/AKT axis. 47 …”
Section: Signaling Pathways In Renal Cancermentioning
confidence: 99%
“…Despite these ambiguities, it is generally accepted that COX-2 exerts a pleiotropic and multifaceted role in carcinogenesis and cancer cell resistance to chemo- and radiotherapy [ 137 ]. The exact mechanisms of COX-2 contribution to RCC are under investigation but involve increased cell proliferation, angiogenesis, matrix metalloproteinase (MMP)-2 expression, invasiveness, and metastasis [ 134 , 138 ].…”
Section: Eicosanoids In Renal Cancermentioning
confidence: 99%
“…Still, in vitro and in vivo data show an association of a COX-2/PGE 2 /EP axis with invasion and metastasis. This is because in addition to the overproduction of PGE 2 , the aberrant expression of its receptors can also amplify PGE 2 signaling, which can facilitate cancer promotion and metastasis [ 138 ]. In particular, EP 2 and EP 4 may play important roles in the malignant behavior of RCC.…”
Section: Eicosanoids In Renal Cancermentioning
confidence: 99%